TAXING POWERS AND DEVELOPMENTAL ROLE OF THE INDIAN STATES : A STUDY WITH REFERENCE TO KERALA - Mohan, R and Shyjan, D (Centre for Development Studies-WP375, 2005)
The study analyses whether the growing State Domestic Product (SDP) of Kerala since the latter half of the 1980s, has acted as a larger resource base for the State and finds that it has not. While the inability to fully tap the existing resource potential could be cited as a reason, the paper argues that the main constraint is the limited taxing powers of the States. The Study concludes that the power to tax the services should be devolved from the Centre to the States, lest the fiscal dispossession should affect the sustainability of achievements, which made the development experience of Kerala unique.